Women and their authentic greatness - Maldonado Alarcón, Rocio (Revista Ciencia y Cultura, 2023)
This article presents an interview by Bolivian journalist, activist, and researcher Vania Sandoval Arenas, following the publication of the book titled “Women in Communication. Bolivia”, of which she is one of the editors and author of a chapter in which she writes about the biography and professional career of Ana María Romero de Campero (the first female Ombudsman in Bolivia). From a gender perspective and supported by the reflections of Simone de Beauvoir, the purpose of this text is to make visible the contributions of Vania and Ana María, emblematic Bolivian women who undoubtedly leave an indelible mark on the construction of a more just and egalitarian society. The dissemination of the stories of illustrious women written by women themselves represents an exercise in resistance that will allow new generations not to forget them. And, above all, that the whole world knows their greatness and their wonderful lives. Likewise, spreading their legacy allows us to recognize and value the immense contribution of women in the contemporary world; especially disputing ideas and knowledge from a female perspective. Writing about women’s experiences allows us to dispute the imaginaries and hegemonic representations that have historically placed women in a submissive or subordinate place and identify ourselves in pioneering and leading female referents.